Evaluasi Kinerja Perawat Pelaksana di Rawat Inap dengan Pendekatan Personal Balance Score Card - Tjiawi, Midoro; Ginting, Chrismis Novalinda; Nasution, Ali Napiah (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate the performance of nurses with the Personal Balance Scorecard approach. The research method uses a cross-sectional study. The results of the study are that there is an effect of the use of a personal balanced scorecard on the quality of performance with a p-value of 0.003, there is an effect of the use of a personal balanced scorecard on work standards with a p-value of 0.021, there is an effect of the use of a personal balanced scorecard on customer perception with a p-value of 0.027, and there is an effect of the use of a personal balanced scorecard on learning and development with a p-value of 0.030. In conclusion, there is a significant effect of the use of a personal balanced scorecard on the quality of performance, work standards, customer perception, and learning and development of adult inpatient nurse performance at Sapta Medika Indrapura Hospital. Keywords: Evaluation, Performance, Personal Balance Score Card